The Influence of The Use of Direct Method in Teaching Reading Comprehension and The Students' Achievement - Lukma Nul Hakim (Tell : Teaching of English Language and Literature Journal, 2019)
Direct method of teaching is a systematic instructional method that first and foremost requires the teacher to have a command of the subject matter at as close to mastery level as possible. This means that whether subject matter is at the elementary level, middle school level, high school level, college level or adult education level, the teacher thoroughly "understands" the content. The main purpose of direct method of teaching is to provide information within a structure that enables all students to attain the stated objectives at a level of mastery. The aim of the research was whether there was any influence between the use of direct method in teaching reading comprehension and the students' achievement in reading comprehension or not. The methods of collecting data were questionnaire, test for reading, and documentary study. The data of this research are analyzed by using "Product Moment Correlation" Person method. The result of calculation of the correlation coefficient between the use of direct method in teaching reading comprehension and the students' achievement up to 0.93. The value of product moment in the table with N = 30 or df = N-2 = 28 in significant 5% is 0.361 and 1 % is 0.463. If this value or rxy is compared with the value of product moment, so 0.361 < 0.93 > 0.463 or rxy > rxyt, it means the value found is bigger than the value in the table. It is a significant correlation between the use of direct method in teaching reading comprehension and the students' achievement.